ANALYSIS OF PROJECT BASED LEARNING WITH THE INTEGRATION OF ARTIFICIAL INTELLIGENCE IN CLASS - Nila Lestari; Hasanah; Nurhafni Siregar (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue:The integration of Artificial Intelligence (AI) into education, particularly in Project-Based Learning (PjBL), is emerging as a strategy to enhance student engagement and 21st- century skills. However, its implementation in elementary schools faces challenges, including teacher preparedness, infrastructure limitations, and ethical considerations. Purpose: This study aims to explore the implementation of AI- supported PjBL in a fifth-grade classroom at UPT SD Negeri 060937 Medan Johor. It seeks to identify the benefits, challenges, and strategies for effective integration of AI in elementary education. Novelty: The research contributes to the relatively limited body of knowledge on how AI can enhance PjBL at the elementary level in Indonesia, particularly in resource-constrained environments. It provides a localized understanding of integrating advanced technologies into foundational education systems. Research Methods: A qualitative case study approach was employed, using interviews, classroom observations, and document analysis. Data were analyzed thematically to identify patterns and insights related to AI integration. Results: The study found that AI integration in PjBL increased student engagement, critical thinking, and collaboration. However, challenges such as technical barriers, teacher adaptation, and ethical concerns were evident. Research Contributions: This study offers practical recommendations for educators and policymakers on leveraging AI in elementary education. It highlights the importance of teacher training, robust infrastructure, and ethical guidelines to ensure AI enhances, rather than hinders, learning outcomes.